The Treatment of Musi River Water Sample using Slow Sand Filter and Ultraviolet Radiation (UV) with Solar Cell Power Sources - Imaniah Sriwijayasih; Eky Novianarenti; Tuty Emilia Agustina; Subriyer Nasir; Rikky Leonard; Tarikh Azis Rand; Imah Luluk Kusminah (Jurnal Engine: Energi, Manufaktur, dan Material, 2024)
The Musi River's water is typically used to meet everyday needs. However, because of the current high population and activities, industrial and domestic garbage are being dumped straight into the Musi River. The purpose of this research was to study the variables that affect the processing of the Musi Riiver Water Samples to get the quality standard requirements of the third-grade river water. Water is filtered using a slow sand filter with a 50–70 cm sand height fluctuation and four different UV irradiation times 15, 30, 45, and 60 minutes. The results of this investigation showed that 2% DO was obtained for the filtration of Musi River water using a slow sand filter with a height of 70 cm sand. BOD5 and COD degradation were determined to be 82% and 93%, respectively. Meanwhile, 29/100 ml of E. Coli was discovered for the UV radiation therapy after a 60-minute irradiation period.